PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 22 PEKANBARU - Meri Asmida; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : The purpose of this research is to improve learning achievement in natural science on fifth grade students at SDN 22 Pekanbaru on academic year 2014/2015 through “the application of problem solving learning’. This research was conducted on March 2015. Subject of the research is fifth grade students SDN 22 pekanbaru, which contain twenty students. There are 15 boys and 5 girls. Type of the research is collaborative classroom action research (teacher works with Researcher). This research contains two cycles. Each cycle consists of 3 meeting. Parameter of this research is student’s achievement after action for each cycle (first and second daily test). Instruments of the research contain learning tools (syllabus, RPP, LKS, learning result paper sheet), students and teacher observation sheet. Data will be analyzed descriptively. Average of students learning achievement increased in which the begining students score of students was 64,5 (very poor). It improved into 75,4 (good) in first daily test. In second daily test the score increased to 83,2 (very good). Average of student activity in first cycle is 65% (enought). And it improved to 85% (very good) in second cycle. Average of teacher activity in first cycle is 65% (enought). And it was improved to 87,5% (very good) in second cycle. Based on the data, researcher concludes the application of Problem Solving learning can improve learning achievement in natural science on Fifth grade students at SDN 22 Pekanbaru.Keyword: problem solving learning, learning achievement of natural science .